2009
DOI: 10.1038/ni.1762
|View full text |Cite
|
Sign up to set email alerts
|

T cell factor 1 initiates the T helper type 2 fate by inducing the transcription factor GATA-3 and repressing interferon-γ

Abstract: The differentiation of activated CD4+ T cells into the T helper type 1 (TH1) or TH2 fate is regulated by cytokines and the transcription factors T-bet and GATA-3. Whereas interleukin 12 (IL-12) produced by antigen-presenting cells initiates the TH1 fate, signals that initiate the TH2 fate are not completely characterized. Here we show that early GATA-3 expression, required for TH2 differentiation, was induced by T cell factor 1 (TCF-1) and its cofactor β-catenin, mainly from the proximal Gata3 promoter upstrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
215
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(232 citation statements)
references
References 49 publications
12
215
1
Order By: Relevance
“…T-bet, a member of the T-box family of transcription factors, has been demonstrated to be involved in polarization toward Th1 cells, while GATA-3 has been demonstrated to be involved in Th2 differentiation (30,31). To further confirm the association between Th1 and Th2 in HBV transgenic mice, real-time PCR and western blot analysis were performed on T cells to assess the expression of T-bet and GATA-3 in the various treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…T-bet, a member of the T-box family of transcription factors, has been demonstrated to be involved in polarization toward Th1 cells, while GATA-3 has been demonstrated to be involved in Th2 differentiation (30,31). To further confirm the association between Th1 and Th2 in HBV transgenic mice, real-time PCR and western blot analysis were performed on T cells to assess the expression of T-bet and GATA-3 in the various treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…All qRT-PCR experiments were performed by using the total RT product from 100 cell equivalents, and results were quantified relative to the mRNA expression levels of the hypoxanthine phosphoribosyltransferase (HPRT) and ␤-actin endogenous reference genes. Primers used in this study included primers described previously for GATA3 (76), E47 (77), HPRT (78), and ACTB (79); forward primer 5=-CAAGGTAGCTTAGCCA ACATGG-3= and reverse primer 5=-GTGGGTGTTGAATTTCATCGGG-3= for RAG1; forward primer 5=-AGTAT TTCACATCCACAAGCAGG-3= and reverse primer 5=-TGACCCACTGTTACCATCTGC-3= for RAG2; forward primer 5=-GGGAATCTTCGACAGCCAGG-3= and reverse primer 5=-AGTTTGAAGAGGAGCAGGCG-3= for PTCRA; forward primer 5=-AGCAGCACTGTGTGCCCTGG-3= and reverse primer 5=-TCTGGGTAGGTAGGGTT GGCTCC-3= for ETS1; forward primer 5=-TTTTGGTGGGTGTTCTTGGC-3= and reverse primer 5=-ACATTGCA TCAGAGACTTGGC-3= for ATM; and forward primer 5=-GAGCCTCCTACTTCCAGTGC-3= and reverse primer 5=-GAAGACATCCTCCTCGCAGC-3= for CCND3.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has demonstrated that GATA3 can be induced in conventional CD4 + T cells following TCR stimulation (38)(39)(40). To assess whether a similar mechanism could account for GATA3 expression by Tregs, highly purified Foxp3 + CD4 + T cells were cocultured with splenic DCs (SpDCs) in the presence of anti-CD3 antibody.…”
Section: Figurementioning
confidence: 99%